Myocarditis in Patients With Antisynthetase Syndrome: Prevalence, Presentation, and Outcomes - Dieval, Céline (Medicine (Baltimore), 2015)
Antisynthetase syndrome (aSS) corresponds to an overlapping inflammatory myopathy identified by various myositis-specific autoantibodies (directed against tRNA-synthetases). Myocardial involvement in this condition is poorly described. From a registry of 352 aSS patients, 12 cases of myocarditis were retrospectively identified on the basis of an unexplained increase in troponin T/I levels associated with either suggestive cardiac magnetic resonance imaging (MRI) findings, nonsignificant coronary artery abnormalities or positive endomyocardial biopsy. The prevalence of myocarditis in aSS is 3.4% and was not linked to any autoantibody specificity: anti-Jo1 (n = 8), anti-PL7 (n = 3), and anti-PL12 (n = 1). Myocarditis was a part of the first aSS manifestations in 42% of the cases and was asymptomatic (n = 2) or revealed by an acute (n = 4) or a subacute (n = 6) cardiac failure. It should be noted that myocarditis was always associated with an active myositis. When performed (n = 11), cardiac MRI revealed a late hypersignal in the T1-images in 73% of the cases (n = 8). Half of the patients required intensive care. Ten patients (83%) received dedicated cardiotropic drugs. Steroids and at least 1 immunosuppressive drug were given in all cases. After a median follow-up of 11 months (range 0–84) 9 (75%) patients recovered whereas 3 (25%) developed a chronic cardiac insufficiency. No patient died. The prevalence of myocarditis in aSS is similar to that of other inflammatory myopathies. Although the prognosis is relatively good, myocarditis is a severe condition and should be carefully considered as a possible manifestation in active aSS patients.